2011
DOI: 10.1021/jp2047272
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Optical and Structural Properties, and Charge Carrier Dynamics of Cu-Doped ZnSe Nanocrystals

Abstract: Stable and luminescent Cu-doped ZnSe nanocrystals (NCs) were synthesized in organic solvents with octadecylamine (ODA) as the capping ligand and characterized using a combination of optical and structural characterization techniques. Successful doping was achieved by adding Cu during the growth phase of the NCs when their size was ∼4 nm. The appearance of red-shifted, intense photoluminescence (PL) peak with doping indicates the incorporation of Cu in the NCs, and stability of dopant emission infers the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
105
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 84 publications
10
105
1
Order By: Relevance
“…Introduction of Cu 2 O or CuO into the glasses as copper source leads to almost identical emission spectra (Figure B). However, it has been reported that the energy gap (ΔE) between the Cu‐state trapping level and the valence band of ZnSe QDs is ~0.7 eV for Cu + dopants and ~0.3 eV for Cu 2+ dopants . Based on the absorption and emission spectra of CU10, CU25 and CU50 glasses, the ΔE values are found to be 0.5‐0.7 eV, very close to the values obtained from Cu + ‐doped ZnSe QDs.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Introduction of Cu 2 O or CuO into the glasses as copper source leads to almost identical emission spectra (Figure B). However, it has been reported that the energy gap (ΔE) between the Cu‐state trapping level and the valence band of ZnSe QDs is ~0.7 eV for Cu + dopants and ~0.3 eV for Cu 2+ dopants . Based on the absorption and emission spectra of CU10, CU25 and CU50 glasses, the ΔE values are found to be 0.5‐0.7 eV, very close to the values obtained from Cu + ‐doped ZnSe QDs.…”
Section: Resultssupporting
confidence: 65%
“…Energy dispersive X‐ray spectroscopic analysis of the nanocrystal marked by white circle in Figure B confirms the presence of zinc, selenide and copper in the nanocrystal marked by the white circle (Figure D). The similar ionic radii between 4 coordinated copper ions (77 pm) and zinc ions (74 pm), and 4 coordinated structure of copper ions and zinc ions in ZnSe nanocrystals as confirmed by extended X‐ray absorption fine structure analysis, indicate that copper ions also substitute the zinc sites in the ZnSe nanocrystals formed in the glass.…”
Section: Resultsmentioning
confidence: 66%
“…It provides an accessible evaluation of absorption of photons, leading to an excitation of an electron from the valence band to the conduction band, which is finally related with the band gap energy (E g ). The band gap energy and Bohr exciton radius of the bulk ZnSe are 2.69 eV (at 461 nm) and 4.5 nm, respectively [26]. From Fig.…”
Section: Topological Studymentioning
confidence: 78%
“…But at 1.5% Fe 2+ doping in the ZnSe, it is observed that the emissions located at 458 and 506 nm. These peaks are shifted to blue end due to more Fe 2+ percent [26]. The emission peaks at 470 nm and 458 nm are due to band to band transitions.…”
Section: Photoluminescencementioning
confidence: 95%
“…Figure 8 shows the absorption of copper-doped zinc selenide quantum dots occurs at 350 nanometers with a blue shift and enhanced absorption compared to zinc selenide quantum dots. The copper-doped zinc selenide quantum dots have been reported to have fewer surface defects, a more compact structure, and better optical properties compared with the undoped zinc selenide quantum dots (Gul et al 2011). …”
mentioning
confidence: 99%